2018
DOI: 10.1038/s41598-018-22520-5
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: ERV1 Overexpression in Myeloid Cells Protects against High Fat Diet Induced Obesity and Glucose Intolerance

Abstract: ERV1tg mice on NCD or HFD for 18 weeks. (j,k) Representative micrographs of liver (j) and VAT (k) stained with hematoxylin and eosin, and Masson's trichrome (k, Bottom row; arrows indicate collagen). (l,n) Weights of livers (l) and single epididymal VAT (n) of WT and ERV1tg mice on NCD or HFD for 18 weeks (n = 4 mice/ group, *P < 0.05 HFD vs. NCD, t test). (m) Fat droplet size in liver of WT and ERV1tg mice on HFD for 18 weeks (n = 4 mice per group, *P < 0.05, t test). (o) Adipocyte size in VAT of mice on HFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(2018) demonstrated that ERV1 reduced body weight and provided protection against HFD-induced hyperglycemia. In addition, the administration of RvE1 reproduced the protective effects of ERV1 overexpression ( Sima et al ., 2018 ). In the same mouse model, endogenous production of SPMs such as RvD1, RvD4, RvD5, PD1, and LXA4 increased, indicating a significant contribution of ERV1 receptor signaling to the regulation of SPM production.…”
Section: Resolution Of Adipose Tissue Inflammation: Effects Of Spms On Obesity-related Metabolic Dysfunctionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2018) demonstrated that ERV1 reduced body weight and provided protection against HFD-induced hyperglycemia. In addition, the administration of RvE1 reproduced the protective effects of ERV1 overexpression ( Sima et al ., 2018 ). In the same mouse model, endogenous production of SPMs such as RvD1, RvD4, RvD5, PD1, and LXA4 increased, indicating a significant contribution of ERV1 receptor signaling to the regulation of SPM production.…”
Section: Resolution Of Adipose Tissue Inflammation: Effects Of Spms On Obesity-related Metabolic Dysfunctionmentioning
confidence: 98%
“…Moreover, the fasting glucose or insulin levels in RvE1 receptor (resolvin E1 receptor [ERV1]/ChemR23) knockout mice were not recovered by RvE1 treatment ( Pal et al ., 2020 ). Using transgenic mice that overexpressed human ERV1 in myeloid cells, Sima et al . (2018) demonstrated that ERV1 reduced body weight and provided protection against HFD-induced hyperglycemia.…”
Section: Resolution Of Adipose Tissue Inflammation: Effects Of Spms On Obesity-related Metabolic Dysfunctionmentioning
confidence: 99%
“…21 Specialized pro-resolving lipid mediators regulate macrophage phenotype favoring pro-healing (M2like) over pro-inflammatory (M1-like) macrophage activation. 34 Resolution pharmacology, as defined by Perretti et al 8…”
Section: Re Soluti On Of Infl Ammati Onmentioning
confidence: 99%
“…21 Specialized pro-resolving lipid mediators regulate macrophage phenotype favoring pro-healing (M2like) over pro-inflammatory (M1-like) macrophage activation. 34 Resolution pharmacology, as defined by Perretti et al 8 and Serhan, 35 is different to traditional anti-inflammatory approaches because specialized pro-resolving lipid mediators are receptor agonists. Thus, prolonged contact with the target and maintaining blood levels is not required, as it is the case with inhibitors or receptor antagonists.…”
Section: Re Soluti On Of Infl Ammati Onmentioning
confidence: 99%
See 1 more Smart Citation